Advance Xp® Male Sling can be an Effective and Safe Treatment for Post-Prostatectomy Stress Urinary Incontinence Also in Patients with Prior History of External Beam Radiation Therapy: A Multicentric Experience. (December 2021) - Li Marzi, Vincenzo; Morselli, Simone; Fusco, Ferdinando; Baldesi, Ramona; Campi, Riccardo; Liaci, Andrea; Gemma, Luca; Morelli, Girolamo; Serni, Sergio
Background. Post-prostatectomy stress urinary incontinence (PPSUI) is one of the major complaints after radical prostatectomy. Transoburator male sling (TMS) placement is indicated in persistent mild to moderate PPSUI. External beam radiation therapy (EBRT) might be a negative prognostic factor for TMS outcomes. Study objective was to analyze EBRT impact on TMS outcome. Methods. We retrospectively investigated patients submitted to TMS for PPSUI, with or without previous EBRT, in two tertiary referral centers since 2010. Objective outcome was measured through ICIQ-SF, 1-hour pad test, and pad per die and subjective improvement through PGI-I. Patients were divided according to EBRT to make in-group and between-group comparisons. Results. Patients were 56, 18 (32.1%) had previous EBRT. Median follow-up was 43.0 months (IQR: 22.3–64.0). TMS was placed at mean 18.8 months (SD 4.6) after EBRT. TMS determined a statistically significant reduction of pads, 1-hour pad test, and ICIQ-SF score ( P <.05). Improvement diminished during long-term follow-up. At last follow-up, 12 patients (21.4%) used 1 safety pad, while 15 (26.8%) used 0 pads. Median PGI-I was 2 (IQR 2–3). Recorded complications were 9 (16.1%) and none exceeded Clavien–Dindo grade 2. There were no differences in outcomes, failures, and complications between groups. TMS failures were 6 (10.7%), 2 of whom in the EBRT group. Four of them (7.1%) subsequently placed an artificial urinary sphincter (AUS). Conclusion . Advance XP© placement seems effective and safe in well-selected patients complaining with PPSUI, even after EBRT. Surgical outcomes slightly deteriorate over time. Further studies are needed in these patients to assess TMS efficacy.